Minimización de funciones convexas sobre la envoltura convexa de un conjunto finito de puntos usando el método de puntos interiores - Gamboa Ferrer, Leydidiana Rosibel (2016)
In this paper we are describe an interior-point method for minimizing a smooth strictly convex function f : Rn → R, on the convex hull P of m points in Rn using the barycentric coordinates for representing points in P and generates points en P . In particular, the algorithm can be use to compute the orthogonal projection of a point zc ∈ Rn hacia P .